Deposit potential and distribution of cobalt and nickel in the sludge of chromite placer mining process at Nui Nua ultramafic massif area, Thanh Hoa province, Vietnam - Ban, To Xuan; Giang, Nguyen Khac; Duc, Tran Van; Dung, Le Tien (Geology, Geophysics and Environment, 2024)
Chromite placer is widely distributed in Quaternary sediments located around the Nui Nua ultramafic massif in Thanh Hoa province, Vietnam. The long-term mining works targeting chromite placer in this area have left a huge amount of waste sludge, up to tens of millions of tons. The paper aims to introduce a deposit potential and distribution of cobalt- and nickel- bearing minerals within the waste sludges generated from the chromite placer mining operations around the mines situated near the Nui Nua ultramafic massif in Thanh Hoa province, Vietnam. Based on field investigations and sample analyses, two groups of waste sludge have been identified: clay-sized sludges and debris waste sludges. The former group is plastic bentonite clay, distributed in depressions and low terrain, and has low contents of cobalt (0.06%) and nickel (0.67%), which is of impractical significance for the recovery purposes of cobalt and nickel. The latter group is usually distributed in relatively high terrain, forming waste sludge ranging from several thousand to hundreds of thousands of tons in volume. These deposits include rock fragments, mineral fragments derived from the Nui Nua ultramafic massif, along with dark spherical nodules rich in goethite, limonite, and Fe-Mn hydroxides, which contain relatively high contents of cobalt (up to 0.75%) and nickel (up to 2.43%) in the waste sludge and chromite placer mines. The cobalt and nickel are mainly concentrated in Fe-Mn nodules made up of goethite, limonite, todorokite, and other Fe-Mn hydroxides. Data from chromite placer explorations, combined with the study results, provide reliable insights into the distribution of cobalt and nickel resources within the waste sludges and chromite placer deposits in the Co Dinh area (northeast of Nui Nua ultramafic massif) and Mau Lam (southwest of Nui Nua massif), Thanh Hoa province. A preliminary estimation of potential resources of Co and Ni metals have been made for the debris waste sludges at Co Dinh and Mau Lam areas based on the ratios of debris particles in the sludges and their contents of Co and Ni along with published resources and reserves of chromite placer ores.